Longitudinal study of single-pulse TMS in infants with perinatal brain injury: safety and feasibility - Collins, Kellie M.; Casey, Cameron P.; Sutter, Ellen N.; DeGrave, Paige; Gauthier, Danielle; Manattu, Arun Karumattu; Cheng, Hung-Shao; McAdams, Ryan M.; Rao, Raghavendra; Georgieff, Michael K.; Gillick, Bernadette T. (Frontiers in Human Neuroscience, 2025)
IntroductionPerinatal brain injury is a leading cause of cerebral palsy. Single-pulse transcranial magnetic stimulation (spTMS) provides a non-invasive method for investigating motor pathway development; however, data on the safety and feasibility of its repeated use in infants are limited. This study provides the first longitudinal evaluation of the safety, tolerability, and feasibility of spTMS in infants with perinatal brain injury.MethodsTwenty infants with perinatal brain injury (corrected age 3–25 months) participated in 46 spTMS sessions while awake. Safety and tolerability were systematically assessed using heart rate, respiratory rate, and the Modified Behavioral Pain Scale (MBPS). Feasibility was quantified by session completion, participant retention, and acquisition of motor-evoked potentials (MEPs) from bilateral wrist flexors.ResultsAcross 2,527 pulses, no adverse events occurred. Physiological measures and MBPS scores remained stable from pre- to post-stimulation. Analyzable electromyography (EMG) was obtained in 100% of sessions, with MEPs successfully elicited in 44/46 sessions (95.7%) across 19/20 infants (95%). A high longitudinal retention rate (85%) further demonstrated excellent protocol acceptability.DiscussionThese findings establish a safe, reproducible framework for longitudinal spTMS in a vulnerable infant population. This methodological advance enables future investigations into neuroplasticity and corticospinal tract development after early brain injury, with the potential to yield biomarkers that guide the timing and targets of early interventions.